In vitro anti-oxidant activity of Ruellia tuberosa root extracts - Chothani, Daya L.; Mishra, S.H. (Free Radicals and Antioxidants)
Background: The present study was aimed to evaluate in vitro anti-oxidant activity of the Ruellia tuberosa (Acanthaceae) roots. Materials and Methods: Anti-oxidant activity was evaluated by using DPPH free radical scavenging activity and reducing power by FeCl3. The methanolic extract (ME), water extract (WE), ethyl acetate extract (EAE) and ethyl acetate fraction of methanol extract (EAFME) of root were tested. The Ascorbic acid was used as positive control. Total phenolic and total flavonoid content were also determined by Folin-Ciocalteu reagent and complementary colorimetric methods (aluminum chloride method and 2, 4-dinitrophenylhydrazine method respectively. Results: The EAFME of root showed the highest concentration of phenolic, flavonoid content, free radical scavenging activity and reducing power. The various extract showed a significant anti-oxidant activity when (P < 0.05) compared with standard. Conclusion: It is concluded that the R. tuberosa root possess anti-oxidant activity. Further studies are suggested to isolate the active principle responsible for the activity.
Keywords: Anti-oxidant activity; DPPH free radical scavenging activity; Ruellia tuberosa; total phenolic